Spillover Effects of Global Markets and the Influence of Fiscal Policy in Indonesia on Rupiah Depreciation (2016–2025) - Siti Aisya; Yuni Prihadi Utomo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the impact of global market spillover effects and the influence of fiscal policy on the depreciation of the Indonesian Rupiah exchange rate during the 2016–2025 period. The variables used include the Rupiah exchange rate (EXR) as the dependent variable, while the Federal Funds Rate (FFR) and global oil prices (OIL) are employed as proxies for external shocks. Meanwhile, tax revenue (TAX) and government expenditure (GOVEXP) represent domestic fiscal policy variables. The analytical method applied in this study is the Domowitz-Elbadawi Error Correction Model (ECM) to capture both short-run and long-run relationships among variables. The findings reveal that in the short run, all independent variables do not significantly affect the Rupiah exchange rate, except government expenditure, which has a positive effect at the 10 percent significance level. In the long run, the variables FFR, TAX, and GOVEXP significantly affect the exchange rate at the 10 percent significance level with a negative relationship, while OIL does not show a significant effect. These findings indicate that the dynamics of the Rupiah exchange rate are more influenced by external factors in the long run, reflecting the presence of spillover effects from global markets, while fiscal policy serves as a stabilization instrument to mitigate external pressures. Therefore, adaptive fiscal policy synergy is required to maintain exchange rate stability amid global economic dynamics.